Pengaruh Dukungan Sosial Terhadap Kecemasan Pada Ibu Hamil di Puskesmas Jetis Kabupaten Ponorogo - Ambika Kurnia Mustikawati (Jurnal Delima Harapan, 2018)
Background: Pregnancy is a valuable thing, but also one of the great stresses for awoman both physically and mentally. Pregnant women with high anxiety will increase therisk of hypertension, difficulty sleeping and stroke, seizures and even death in the motherand fetus. In Puskesmas Ponorogo district the number of pregnant women as much as5903 mothers, while in health centers Jetis the number of pregnant women as many as200 mothers. Interview results, 21 out of 27 mothers said were very anxious during herpregnancy. The purpose of this study was to analyze the factors of social support foranxiety in pregnant women.Subjects and Methods: The type of research is analytical with cross-sectional approach.The location of research at Jetis health center Ponorogo regency. Research conducted onSeptember 1 to October 15, 2016. Sample of 30 pregnant women using proportionalrandom sampling technique. Dependent variable is anxiety, while independent variable issocial support. Data collection techniques using questionnaires. Data analysis usingSpearman's Rho using SPSS 18.0 for windows computer program.Results: The results showed that from 40 respondents, almost half were 13 (32.5%)multiparous had mild anxiety and nearly half were 13 (32.5%) primipara experiencedmoderate anxiety. of the 40 respondents, nearly half (12%) of 3 trimester pregnantwomen had moderate anxiety and a small proportion of 9 (22.5%) of 2 trimester pregnantwomen had mild anxiety. The result of calculation using spearman's rho statistic testobtained p = 0,006 <α 0,05 mean there is influence between parity with anxiety inpregnant woman with correlation coefficient of -0,424 which show intensity of influenceof medium that is if the smaller parity hence more anxiety level. The calculation ofgestational age with spearman's rho p = 0,023 <α 0.05 means that there is an influencebetween parity with anxiety in pregnant women with a correlation coefficient of 0.359which shows the weakness of weak influence.Conclusion: The social support provided by husband and family will affect the level ofanxiety in each pregnant woman. It is hoped for a place of research to provide a solutionfor pregnant women who experience anxiety so that pregnancy can run smoothly andrespondents are expected to have a good coping mechanism in the face of anxiety forhealth and also the fetus.